Mathematics Communication Skill Seen from Self-Efficacy of Junior High School Students on 7E Learning Cycle with Ethnomathematics Nuances - Hasanah, Uswatun (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe mathematics communication skill seen from self-efficacy on high, moderate, and low categories. It was done for VII graders of Public Junior High School 1 Takengon in academic year 2018/2019. This mixed method research used sequential explanatory strategy. It is a procedure to collect quantitative and qualitative data orderly. The findings showed that the model was effective to improve mathematics communication skill of the students. mathematics communication skill and self-efficacy of each category has different mastery indicators. The differences occurred because students had different developments. Therefore, learning should be undertaken based on their capabilities to understand and needed self-regulation of the students which should be supported by environment.